2020
DOI: 10.3892/mmr.2020.11281
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential markers for type 2 diabetes mellitus via bioinformatics analysis

Abstract: Type 2 diabetes mellitus (T2dM) is a multifactorial and multigenetic disease, and its pathogenesis is complex and largely unknown. in the present study, microarray data (GSe201966) of β-cell enriched tissue obtained by laser capture microdissection were downloaded, including 10 control and 10 type 2 diabetic subjects. a comprehensive bioinformatics analysis of microarray data in the context of protein-protein interaction (PPi) networks was employed, combined with subcellular location information to mine the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 116 publications
(124 reference statements)
2
13
0
Order By: Relevance
“…The reconstruction and analysis of gene networks is a widely used approach for studying the mechanisms of complex biological processes and multifactorial diseases [ 25 , 26 ]. Specifically, this approach was applied for identification of key genes and pathways involved in pathogenesis of diabetes and its complications [ 27 , 28 , 29 , 30 ]. However, to our knowledge, GV-related networks have not been reconstructed and analyzed yet.…”
Section: Introductionmentioning
confidence: 99%
“…The reconstruction and analysis of gene networks is a widely used approach for studying the mechanisms of complex biological processes and multifactorial diseases [ 25 , 26 ]. Specifically, this approach was applied for identification of key genes and pathways involved in pathogenesis of diabetes and its complications [ 27 , 28 , 29 , 30 ]. However, to our knowledge, GV-related networks have not been reconstructed and analyzed yet.…”
Section: Introductionmentioning
confidence: 99%
“…All others do not have enough data to determine whether they are expressed or not in the brain. Only four were previously associated with any neurological disease or with AD risk factors: hsa-miR-373-5p with schizophrenia ( Pala and Denkçeken, 2020 ); hsa-miR-657 with type 2 diabetes ( Lv et al, 2008 ); hsa-miR-192-5p with venous thrombosis and type 2 diabetes ( Lu et al, 2020 ; Rodriguez-Rius et al, 2020 ); and has-miR-147b with negative regulation of the inflammatory response ( van Scheppingen et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…miR-92a-3p regulates insulin biosynthesis [ 43 ], and has a role in insulin secretion by pancreatic β cells [ 44 ], and in insulin stimulated glucose uptake by skeletal muscle [ 8 ]. MiR-192-5p appears to be involved in type 2 diabetes (T2DM) by regulating the expression of several genes involved in T2DM, such as procollagen C-endopeptidase enhancer 2 (PCOLCE2), which is significantly decreased in T2DM [ 45 , 46 ]. In healthy uncomplicated pregnancies miR-451a is constitutively expressed [ 41 ] however, our study found upregulation in the first trimester of pregnancies that went on to be diagnosed with GDM.…”
Section: Discussionmentioning
confidence: 99%